Correlating blast vibrations and geomechanical properties to determine damage profiles and improve wall conditions in open pit mining - LOPES,GUSTAVO S. (2022)
Abstract Slope stability is one of the biggest concerns for mining practices and to consider the rock mass response over blasting is fundamental to achieve pit geometry. This study consists in developing a methodology which connects the dynamic behavior of one lithological domain to blast designs applied at a copper mine. The central element of this study was the construction of vibration attenuation and seed wave model which, in conjunction with geomechanical properties, has allowed the characterization of this particular rock mass and the vibration attenuation phenomena. The new blast design was developed from the model simulations, once it was possible to recognize which parameters of the blast design affect most of the damage induced by blasting. To guarantee model representativeness, two blast tests were conducted: one with the usual blast design and another using the new one. Furthermore, holes were drilled behind the blasts, which were inspected before and after each blast to compare the produced fracturing with the fracturing expected by the model. The results obtained in these blast tests show a strong correlation between the modeled and the real. The modeling proved to be a useful tool providing manners to stablish a blast design, which generates stable walls.